2016
DOI: 10.14202/vetworld.2016.403-409
|View full text |Cite
|
Sign up to set email alerts
|

Maggot debridement therapy as primary tool to treat chronic wound of animals

Abstract: Maggot debridement therapy (MDT) is a safe, effective, and controlled method ofhealing of chronic wounds by debridement and disinfection. In this therapy live, sterile maggots of green bottle fly, Lucilia (Phaenicia) sericata are used, as they prefernecrotic tissues over healthy for feeding. Since centuries, MDT is used in humanbeings to treat chronic wounds. Lately, MDT came out as a potent medical aid in animals. In animals, although, this therapy is still limited and clinical studies are few. However, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…These flies are famous for their success in wound healing throughout history. Today, maggot debridement therapy (MDT) is approved by the FDA (Choudhary et al 2016). It has been shown that besides removal of necrotic tissue and pathogens, maggots help healing by their antimicrobial activity (Andersen et al 2010).…”
mentioning
confidence: 99%
“…These flies are famous for their success in wound healing throughout history. Today, maggot debridement therapy (MDT) is approved by the FDA (Choudhary et al 2016). It has been shown that besides removal of necrotic tissue and pathogens, maggots help healing by their antimicrobial activity (Andersen et al 2010).…”
mentioning
confidence: 99%
“…In 2004, the Food and Drug Administration (FDA) granted permission and approved maggots as a medical device to be marketed for wound care (Sherman, 2005;Andersen et al, 2010;Cazander et al, 2010;Choudhary et al, 2016;and Yan et al, 2018) which has been prescribed for patients in more than 200 hospitals in the USA. It was reported that thousands of patients have been treated by this method (Mumcuoglu, 2001) as for e.g., some 20,000 patients throughout the UK have benefited from MT (Brindley.…”
Section: Results and Discussion Brief History And Current Statusmentioning
confidence: 99%
“…2011). Maggots are applied on the wound in two-ways (Choudhary et al, 2016): the free-range dressing (direct contact method) and the biobag dressing (indirect contact method) (Janssen, 2005;Jones and Wall, 2007;Lepage et al 2012 andBrown, 2013).…”
Section: Methods Of Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-embryonic stages of Phaenicia sericata fly are facultative parasites of birds and mammals, feeding on their living tissues in a process called myiasis. The development of the larvae lasts about 20 days, so the wounds in which flies lay their eggs must heal quickly [33,34]. As it turns out, sounds can also be used to heal wounds.…”
Section: Future Perspectivesmentioning
confidence: 99%